Design and Methods of the New Zealand National Gambling Study, a Prospective Cohort Study of Gambling and Health: 2012-2019. - Abbott, Max; Bellringer, Maria; Garrett, Nick; Kolandai-Matchett, Komathi (International Journal of Mental Health & Addiction, 2017)
This paper describes the design, sampling, recruitment, and data analysis of the prospective, nationally representative New Zealand National Gambling Study. Particular aspects of the study were critical for its success as a longitudinal epidemiologic study, making its methodology beneficial for replication in other jurisdictions. At baseline (2012), 6251 adults were interviewed and followed-up in 2013, 2014, and 2015. An additional cohort of 106 moderate-risk/problem gamblers interviewed at baseline (2014-2015) and follow-up (2015-2016) increased the number of these groups in the study. Measures included gambling commencement, gambling frequency, gambling risk levels, at-risk and problem gambling development (incidence), comorbidity, problem gambling cessation, and relapse. Future stages include a follow-up assessment in 2019 and a qualitative study. The study design enables assessment of population and individual level changes and transitions over time, identification of risk and protective factors, and comparisons with previous similarly designed prospective studies. Methods for enhancing response rates and retention are discussed.